An assessment of the Lesotho government assistance programmes in addressing the financial implications of education for all at secondary school level : a case study of two secondary schools. - Mohoebi, Matseliso Alice (My University, 2014)
The study assesses the Lesotho government’s assistance programmes in addressing the financial implications of Education for All (EFA) at secondary school level. It does this by examining the objectives of the financial assistance programmes, their main problems and tensions in the implementation, and how they impact on the education of poor learners. This research was conducted using a qualitative methodology, which relied in part on the case study approach by focusing on two schools in the poor areas of Lesotho. The study used a multi-method data collection approach with interviews, questionnaires and document analysis. The respondents were selected on the basis of their relationship to the implementation of these government programmes. The school sample comprised two (2) principals, four (4) parents of learners targeted by such assistance programmes, and four (4) teachers working with learners who were beneficiaries of these programmes and who knew how these programmes assisted them (or not). There were two MOET officials, the bursary manager at central level, responsible for all government assistance programmes; and the district education bursary administrator responsible for the OVC programmes and entrusted with implementing the programmes in line with the regulations. The decision to get information from these respondents was because they were knowledgeable or experienced in different aspects of these government programmes, their implementation, and the impact on schools and learners. ii Using the rational and political analytical approaches, the findings reveal the limited conceptualization of the financial assistance programmes designed to widen the secondary education of poor learners as these did not address the deeper problems of Orphans and Vulnerable Children’s (OVC) problems in accessing and completing their education. The rational approach indicates poor system resources and capacity to effectively manage these programmes, as well as poor monitoring and accountability at all levels of the system. The political approach emphasises the poor implementation context of these assistance programmes due to the conflicting agendas of various programme implementers. The role of leadership is identified as crucial in interpreting and effectively mediating the operationalisation of these programmes on the ground so that the more deserving poor learners benefit. However, such leadership appears to be lacking at various levels of the implementation process. The study concludes that in order for these government assistance programmes to have a lasting and meaningful impact on OVC secondary schooling, there is a need to review their assumptions and scope to address more fully the OVC needs. Additional resource mobilization coupled with strong leadership, monitoring and evaluation are necessary for this to be realised.
Keywords: Secondary schooling; Access and Completion; Orphans and Vulnerable Children; Government Assistance Programmes